The impact of senior house developments on surrounding residential property values. Issue 5 (17th October 2016) - Kurvinen, Antti Tapio; Tyvimaa, Tanja
Abstract : Purpose: Even as many countries are facing changes in demographic profile and new types of senior housing developments are becoming more important, there is limited evidence for the development impact of a senior house on surrounding residential property values. The purpose of this paper is to address the void in knowledge, investigating the impact of senior house developments on apartment values in Tampere, Finland. Design/methodology/approach: To specify valuation effects of proximate senior house development projects, advanced research design combining propensity score matching procedure and hedonic pricing models is used. Findings: The results show that a senior house development has a significant positive impact on proximate residential property values within a 500 metre radius. The impact is found to be the highest in underdeveloped neighbourhoods. Nevertheless, in neighbourhoods where property values and demand for housing units are higher and senior house developments fall into the criteria of infill development, a premium is lower, but still statistically significant and notable in magnitude. Research limitations/implications: This paper studies apartment values only in Tampere, Finland, and it is important to notice that local regulations and market conditions may have a notable impact on the outcomes from senior house developments. Originality/value: This study is the first of its kind to address a number of empirical issues and provide with statistically significant evidence for positive impacts from senior house developments – encouraging investors and developers to build senior houses.